Stage Directions Beyond Theater: Eugène Ionesco’s exercise in theatricality - Pereira (Universidade Federal do Paraná – UFPR, Curitiba/PR, Brazil), Viviane Araujo Alves da Costa (Revista Brasileira de Estudos da Presença, 2022)
Stage directions are a special type of genre in theater, ranging from indications for the dramatic text to the emergence of the author’s voice. In Eugène Ionesco’s case, stage directions go beyond his plays and find another function in his critical writings and in his correspondence with directors. In this paper, we analyze how stage directions function in the texts published in Notes et contre-notes and in the manuscripts housed in Ionesco’s Archives, from the perspective of a theoretical debate that involves Bernard Dort, Roland Barthes and Luiz Fernando Ramos, among other researchers interested in theatricality.